2022
DOI: 10.3390/jcm11247340
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Facio-Dental Proportions to Determine the Width of Maxillary Anterior Teeth: A Clinical Study

Abstract: The present study aimed to analyze mid horizontal facial third proportions, those being the interpupillary, inner intercanthal, and bizygomatic distance modified with golden proportion, The Preston proportion, golden percentage and 70% recurring esthetic dental proportion were used for determining maxillary anterior teeth width. A total of 230 participants took part in this study. The front dental and facial photographs along dental stone cast which were converted to three-dimensional (3D) models were used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, predicting central incisor width with 70% RED proportions and inter-alar distance is an accurate method to evaluate the width of maxillary anterior teeth [62] using specific formulas. A recent study [63] also identified formulas to determine central incisor width by modifying inner-canthal distance according to Golden Percentage, and interpupillary distance according to Golden Proportions. The Golden Rectangle theory, as suggested by a few articles found in the literature, seems to be applicable to the Indian populations investigated in the studies, both in men and women [64][65][66].…”
Section: Anterior Teeth Dimensionsmentioning
confidence: 99%
“…However, predicting central incisor width with 70% RED proportions and inter-alar distance is an accurate method to evaluate the width of maxillary anterior teeth [62] using specific formulas. A recent study [63] also identified formulas to determine central incisor width by modifying inner-canthal distance according to Golden Percentage, and interpupillary distance according to Golden Proportions. The Golden Rectangle theory, as suggested by a few articles found in the literature, seems to be applicable to the Indian populations investigated in the studies, both in men and women [64][65][66].…”
Section: Anterior Teeth Dimensionsmentioning
confidence: 99%